Hubungan antara perilaku membawa bekal, frekuensi konsumsi jajan, tingkat kecukupan zat gizi makro terhadap status gizi pada anak sekolah dasar - Saniah Siregar; Iswahyudi Iswahyudi; Rahmatika Nur Aini (Poltekkes Kemenkes Aceh, 2025)
Background: The school years are an important period in the growth and development of children towards adolescence, which is vulnerable to nutritional disorders. Nutritional disorders are mainly caused by unbalanced and excessive food consumption. The habit of bringing lunch is a significant factor in increasing food intake to meet the nutritional needs of elementary school children.Objectives: This study aims to analyze the relationship between the habit of bringing lunch, frequency of snack consumption, and macronutrient adequacy with the nutritional status of students at SDN Pinang 01 Tangerang City. Methods: This study used descriptive quantitative method with cross-sectional design, involving dependent and independent variables. The independent variable is nutritional status, while the dependent variable includes the behavior of bringing lunch, the frequency of snacks consumption, and the adequacy of macronutrients in elementary school students. The questionnaires used were 2x24 hour food recall forms to see the adequacy of macronutrients, FFQ forms to see snacking habits and open interviews to see students' habits in bringing lunch.Results: The results showed a relationship between the behavior of bringing lunch with nutritional status (p value = 0,000), frequency of snacks consumption (p value = 0,000), adequacy of energy intake (p value = 0,000), adequacy of protein intake (p value = 0,002), adequacy of fat intake (p value = 0,001), and adequacy of carbohydrate intake (p value = 0,000).Conclusion: There is an association between behavior.